Fully-Featured Anonymous Credentials with Reputation System - Bemmann, Kai; Blömer, Johannes; Bobolz, Jan; Bröcher, Henrik; Diemert, Denis Pascal; Eidens, Fabian; Eilers, Lukas; Haltermann, Jan Frederik; Juhnke, Jakob; Otour, Burhan; Porzenheim, Laurens Alexander; Pukrop, Simon; et al. (Proceedings of the 13th International Conference on Availability, Reliability and Security - ARES '18)
We present CLARC (Cryptographic Library for Anonymous Reputation and Credentials), an anonymous credentials system (ACS) combined with an anonymous reputation system. Using CLARC, users can receive attribute-based credentials from issuers. They can efficiently prove that their credentials satisfy complex (access) policies in a privacy-preserving way. This implements anonymous access control with complex policies. Furthermore, CLARC is the first ACS that is combined with an anonymous reputation system where users can anonymously rate services. A user who gets access to a service via a credential, also anonymously receives a review token to rate the service. If a user creates more than a single rating, this can be detected by anyone, preventing users from spamming ratings to sway public opinion. To evaluate feasibility of our construction, we present an open-source prototype implementation.

Designing Multi-sided Community Platforms for Local High Street Retail - Bartelheimer, Christian; Hendrik Betzing, Jan; Berendes, Ingo; Beverungen, Daniel (Proceedings of the 26th European Conference on Information Systems)

Design Principles for Co-Creating Digital Customer Experience in High Street Retail - Hendrik Betzing, Jan; Beverungen, Daniel; Becker, Jörg (Tagungsband Data driven X --- Turning Data into Value --- Band V)

Kundenbewertungen und Produktnachfrage: Eine ökonomische Analyse - Maurer, Alexandra

The Segmentation of Video-On-Demand Consumers - Michels, Luisa Juliane

Sentiment Analysis of User-generated Ratings in the Sharing Economy - Walter, Miriam

Restaurant reputation and meal prices: empricial evidence from the German restaurant industry - Korn, Hanna

Korrektheitsbeweise für Muster von Servicekompositionen - Rautenberg, Kai

Let the state follow its flows: An SDN-based flow handover protocol to support state migration - Peuster, Manuel; Küttner, Hannes; Karl, Holger (4th IEEE International Conference on Network Softwarization (NetSoft 2018))
Dynamically steering flows through virtualized net- work function instances is a key enabler for elastic, on-demand deployments of virtualized network functions. This becomes par- ticular challenging when stateful functions are involved, necessi- tating state management. The problem with existing solutions is that they typically embrace state migration and flow rerouting jointly, imposing a huge set of requirements on the on-boarded VNFs, e.g., solution-specific state management interfaces. In this paper, we introduce the seamless handover proto- col (SHarP). It provides an easy-to-use, loss-less, and order- preserving flow rerouting mechanism that is not fixed to a single state management approach. This allows VNF vendors to implement or use the state management solution of their choice. SHarP supports these solutions with additional information when flows are migrated. Further, we show how SHarP significantly reduces the buffer usage at a central (SDN) controller, which is a typical bottleneck in existing solutions. Our experiments show that SHarP uses a constant amount of controller buffer, irrespective of the time taken to migrate the VNF state.

Containernet 2.0: A Rapid Prototyping Platform for Hybrid Service Function Chains - Peuster, Manuel; Kampmeyer, Johannes; Karl, Holger (4th IEEE International Conference on Network Softwarization (NetSoft 2018))
Developing a virtualized network service does not only involve the implementation and configuration of the network functions it is composed of but also its integration and test with management solutions that will control the service in its production environment. These integration tasks require testbeds that offer the needed network function virtualization infrastructure~(NFVI), like OpenStack, introducing a lot of management and maintenance overheads. Such testbed setups become even more complicated when the multi point-of-presence~(PoP) case, with multiple infrastructure installations, is considered. In this demo, we showcase an emulation platform that executes containerized network services in user-defined multi-PoP topologies. The platform does not only allow network service developers to locally test their services but also to connect real-world management and orchestration solutions to the emulated PoPs. During our interactive demonstration we focus on the integration between the emulated infrastructure and state-of-the-art orchestration solutions like SONATA or OSM.

Emulation-based Smoke Testing of NFV Orchestrators in Large Multi-PoP Environments - Peuster, Manuel; Marchetti, Michael; Garcia de Blas, Gerado; Karl, Holger (European Conference on Networks and Communications (EuCNC))
Management and orchestration~(MANO) systems are the key components of future large-scale NFV environments. They will manage resources of hundreds or even thousands of NFV infrastructure installations, so called points of presence~(PoP). Such scenarios need to be automatically tested during the development phase of a MANO system. This task becomes very challenging because large-scale NFV testbeds are hard to maintain, too expensive, or simply not available. In this paper, we present a multi-PoP NFV infrastructure emulation platform that enables automated, large-scale testing of MANO stacks. We show that our platform can easily emulate hundreds of PoPs on a single physical machine and reduces the setup time of a test PoP by a factor of 232x compared to a DevStack-based test PoP installation. Further, we present a case study in which we test ETSI's Open Source MANO~(OSM) against our proposed system to gain insights about OSM's behaviour in large-scale NFV deployments.

Ampehre: An Open Source Measurement Framework for Heterogeneous Compute Nodes - Lösch, Achim; Wiens, Alex; Platzner, Marco (Proceedings of the International Conference on Architecture of Computing Systems (ARCS))
Profiling applications on a heterogeneous compute node is challenging since the way to retrieve data from the resources and interpret them varies between resource types and manufacturers. This holds especially true for measuring the energy consumption. In this paper we present Ampehre, a novel open source measurement framework that allows developers to gather comparable measurements from heterogeneous compute nodes, e.g., nodes comprising CPU, GPU, and FPGA. We explain the architecture of Ampehre and detail the measurement process on the example of energy measurements on CPU and GPU. To characterize the probing effect, we quantitatively analyze the trade-off between the accuracy of measurements and the CPU load imposed by Ampehre. Based on this analysis, we are able to specify reasonable combinations of sampling periods for the different resource types of a compute node.

Static Scheduling Algorithms for Heterogeneous Compute Nodes - Schnuer, Jan-Philip

Evaluation of OpenCL-based Compilation for FPGAs - Croce, Marcel

An FPGA/HMC-Based Accelerator for Resolution Proof Checking - Hansmeier, Tim; Platzner, Marco; Andrews, David (ARC 2018: Applied Reconfigurable Computing. Architectures, Tools, and Applications)
Modern Boolean satisfiability solvers can emit proofs of unsatisfiability. There is substantial interest in being able to verify such proofs and also in using them for further computations. In this paper, we present an FPGA accelerator for checking resolution proofs, a popular proof format. Our accelerator exploits parallelism at the low level by implementing the basic resolution step in hardware, and at the high level by instantiating a number of parallel modules for proof checking. Since proof checking involves highly irregular memory accesses, we employ Hybrid Memory Cube technology for accelerator memory. The results show that while the accelerator is scalable and achieves speedups for all benchmark proofs, performance improvements are currently limited by the overhead of transitioning the proof into the accelerator memory.

On the effectiveness of heuristics for learning nested dichotomies: an empirical analysis - Melnikov, Vitalik; Hüllermeier, Eyke (Machine Learning)
In machine learning, so-called nested dichotomies are utilized as a reduction technique, i.e., to decompose a multi-class classification problem into a set of binary problems, which are solved using a simple binary classifier as a base learner. The performance of the (multi-class) classifier thus produced strongly depends on the structure of the decomposition. In this paper, we conduct an empirical study, in which we compare existing heuristics for selecting a suitable structure in the form of a nested dichotomy. Moreover, we propose two additional heuristics as natural completions. One of them is the Best-of-K heuristic, which picks the (presumably) best among K randomly generated nested dichotomies. Surprisingly, and in spite of its simplicity, it turns out to outperform the state of the art.

JMCTest: Automatically Testing Inter-Method Contracts in Java - Börding, Paul; Haltermann, Jan Frederik; Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the IFIP International Conference on Testing Software and Systems (ICTSS 2018))
Over the years, Design by Contract (DbC) has evolved as a powerful concept for program documentation, testing, and verification. Contracts formally specify assertions on (mostly) object-oriented programs: pre- and postconditions of methods, class invariants, allowed call orders, etc. Missing in the long list of properties specifiable by contracts are, however, method correlations: DbC languages fall short on stating assertions relating methods. In this paper, we propose the novel concept of inter-method contract, allowing precisely for expressing method correlations.We present JMC as a language for specifying and JMCTest as a tool for dynamically checking inter-method contracts on Java programs. JMCTest fully automatically generates objects on which the contracted methods are called and the validity of the contract is checked. Using JMCTest, we detected that large Java code bases (e.g. JBoss, Java RT) frequently violate standard inter-method contracts. In comparison to other verification tools inspecting (some) inter-method contracts, JMCTest can find bugs that remain undetected by those tools.

Breaking the $\tildeΩ(\sqrt{n})$ Barrier: Fast Consensus under a Late Adversary - Robinson, Peter; Scheideler, Christian; Setzer, Alexander (Proceedings of the 30th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
We study the consensus problem in a synchronous distributed system of n nodes under an adaptive adversary that has a slightly outdated view of the system and can block all incoming and outgoing communication of a constant fraction of the nodes in each round. Motivated by a result of Ben-Or and Bar-Joseph (1998), showing that any consensus algorithm that is resilient against a linear number of crash faults requires $\tilde Ω(\sqrt n)$ rounds in an n-node network against an adaptive adversary, we consider a late adaptive adversary, who has full knowledge of the network state at the beginning of the previous round and unlimited computational power, but is oblivious to the current state of the nodes. Our main contributions are randomized distributed algorithms that achieve consensus with high probability among all except a small constant fraction of the nodes (i.e., "almost-everywhere'') against a late adaptive adversary who can block up to ε n$ nodes in each round, for a small constant ε >0$. Our first protocol achieves binary almost-everywhere consensus and also guarantees a decision on the majority input value, thus ensuring plurality consensus. We also present an algorithm that achieves the same time complexity for multi-value consensus. Both of our algorithms succeed in $O(log n)$ rounds with high probability, thus showing an exponential gap to the $\tildeΩ(\sqrt n)$ lower bound of Ben-Or and Bar-Joseph for strongly adaptive crash-failure adversaries, which can be strengthened to $Ω(n)$ when allowing the adversary to block nodes instead of permanently crashing them. Our algorithms are scalable to large systems as each node contacts only an (amortized) constant number of peers in each communication round. We show that our algorithms are optimal up to constant (resp.\ sub-logarithmic) factors by proving that every almost-everywhere consensus protocol takes $Ω(log_d n)$ rounds in the worst case, where d is an upper bound on the number of communication requests initiated per node in each round. We complement our theoretical results with an experimental evaluation of the binary almost-everywhere consensus protocol revealing a short convergence time even against an adversary blocking a large fraction of nodes.
Keywords: distributed consensus; randomized algorithm; adaptive adversary; complexity lower bound

ML-Plan: Automated Machine Learning via Hierarchical Planning - Mohr, Felix; Wever, Marcel Dominik; Hüllermeier, Eyke (Machine Learning)
Automated machine learning (AutoML) seeks to automatically select, compose, and parametrize machine learning algorithms, so as to achieve optimal performance on a given task (dataset). Although current approaches to AutoML have already produced impressive results, the field is still far from mature, and new techniques are still being developed. In this paper, we present ML-Plan, a new approach to AutoML based on hierarchical planning. To highlight the potential of this approach, we compare ML-Plan to the state-of-the-art frameworks Auto-WEKA, auto-sklearn, and TPOT. In an extensive series of experiments, we show that ML-Plan is highly competitive and often outperforms existing approaches.
Keywords: AutoML; Hierarchical Planning; HTN planning; ML-Plan

Triadic relationships in the context of services for animal companions - Rötzmeier-Keuper, Julia; Hendricks, Jennifer; Wünderlich, Nancy; Schmitz, Gertrud (Journal of Business Research)
Triadic service relationships comprise complex relationships in which not only the customer and provider are involved as partners but also other individuals with caregiving relationships with the customer. A triadic constellation may arise in the context of services for animal companions, for example, when veterinarians provide counsel and treatment to the animal companion and its owner. Through interviews with both owners of animal companions and providers of services for animal companions, this study explores typical constellations and characteristics of the three relationships in this service triad. In line with balance theory, the results show that four distinct types of triadic relationships exist in services for animal companions: the harmonious, the dysfunctional, the challenging, and the doubtful triad. The study highlights the potential conflicts and dynamics in the triads to advise providers on how to address customers depending on the types of triads to which they belong.
Keywords: Triadic relationships; Balance theory; Pet-related services; Animal companions; Service relationship typology; Service triads

About the Fear of Reputational Loss: Social Trading and the Disposition Effect - Pelster, Matthias; Hofmann, Annette (Journal of Banking & Finance)

FastLane Is Opaque – a Case Study in Mechanized Proofs of Opacity - Schellhorn, Gerhard; Wedel, Monika; Travkin, Oleg; König, Jürgen; Wehrheim, Heike (Software Engineering and Formal Methods)

Design Options of Store-Oriented Software Ecosystems: An Investigation of Business Decisions - Jazayeri, Bahar; Zimmermann, Olaf; Engels, Gregor; Küster, Jochen; Kundisch, Dennis; Szopinski, Daniel (Proceeding of International Symposium on Business Modeling and Software Design)
Nowadays companies like Apple create ecosystems of third- party providers and users around their software platforms. Often online stores like Apple App Store are created to directly market third-party solutions. We call such ecosystems store-oriented software ecosystems. While the architecture of these ecosystems is mainly derived from busi- ness decisions of their owners, ecosystems with greatly different archi- tectural designs have been created. This diversity makes it challenging for future ecosystem providers to understand which architectural design is suitable to fulfill certain business decisions. In turn, opening a plat- form becomes risky while endangering intellectual property or scarifying quality of services. In this paper, we identify three main design options of store-oriented software ecosystems by classifying existing ecosystems based on similarities in their business decisions. We elaborate on the design options, discuss their main contributions, and provide exemplary ecosystems. Our work provides aspiring ecosystem providers with the reusable knowledge of existing ecosystems and helps them to take more informed architectural decisions and reduce risks in future.

Scheduling with interjob communication on parallel processors - König, Jürgen; Mäcker, Alexander; Meyer auf der Heide, Friedhelm; Riechers, Sören (Journal of Combinatorial Optimization)

Reduction Stumps for Multi-Class Classification - Mohr, Felix; Wever, Marcel Dominik; Hüllermeier, Eyke (Proceedings of the Symposium on Intelligent Data Analysis)

CIRCA: Towards a Modular and Extensible Framework for Approximate Circuit Generation - Witschen, Linus Matthias; Wiersema, Tobias; Ghasemzadeh Mohammadi, Hassan; Awais, Muhammad; Platzner, Marco (Third Workshop on Approximate Computing (AxC 2018))
Existing approaches and tools for the generation of approximate circuits often lack generality and are restricted to certain circuit types, approximation techniques, and quality assurance methods. Moreover, only few tools are publicly available. This hinders the development and evaluation of new techniques for approximating circuits and their comparison to previous approaches. In this paper, we ﬁrst analyze and classify related approaches and then present CIRCA, our ﬂexible framework for search-based approximate circuit generation. CIRCA is developed with a focus on modularity and extensibility. We present the architecture of CIRCA with its clear separation into stages and functional blocks, report on the current prototype, and show initial experiments.
Keywords: Approximate Computing; Framework; Pareto Front; Accuracy

Solving Maxwell's Equations with Modern C++ and SYCL: A Case Study - Afzal, Ayesha; Schmitt, Christian; Alhaddad, Samer; Grynko, Yevgen; Teich, Jürgen; Förstner, Jens; Hannig, Frank (Proceedings of the 29th Annual IEEE International Conference on Application-specific Systems, Architectures and Processors (ASAP))
In scientific computing, unstructured meshes are a crucial foundation for the simulation of real-world physical phenomena. Compared to regular grids, they allow resembling the computational domain with a much higher accuracy, which in turn leads to more efficient computations. There exists a wealth of supporting libraries and frameworks that aid programmers with the implementation of applications working on such grids, each built on top of existing parallelization technologies. However, many approaches require the programmer to introduce a different programming paradigm into their application or provide different variants of the code. SYCL is a new programming standard providing a remedy to this dilemma by building on standard C ++17 with its so-called single-source approach: Programmers write standard C ++ code and expose parallelism using C++17 keywords. The application is then transformed into a concrete implementation by the SYCL implementation. By encapsulating the OpenCL ecosystem, different SYCL implementations enable not only the programming of CPUs but also of heterogeneous platforms such as GPUs or other devices. For the first time, this paper showcases a SYCL- based solver for the nodal Discontinuous Galerkin method for Maxwell’s equations on unstructured meshes. We compare our solution to a previous C-based implementation with respect to programmability and performance on heterogeneous platforms.<br
Keywords: tet_topic_hpc

Supporting the Change to Digitalized Production Environments Through Learning Organization Development - Fischer, Christoph; Pöhler, Alexander (The Impact of Digitalization in the Workplace)
Keywords: i40

Wissensmanagement unter Bedingungen von Arbeit 4.0 - Harteis, Christian; Fischer, Christoph (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)
Keywords: i40; learning culture

Digitalisation of Work: Between Affordances and Constraints for Learning at Work - Fischer, Christoph; Goller, Michael; Brinkmann, Lorraine; Harteis, Christian (Digital Workplace Learning)
Keywords: i40; learning culture

Individual and social influences on professional learning. Supporting the acquisition and maintenance of expertise. - Gruber, Hans; Harteis, Christian

The impact of digitalization in the workplace: an educational view

Machines, Change and Work: An Educational View on the Digitalization of Work - Harteis, Christian (The Impact of Digitalization in the Workplace)

Developing Occupational Expertise through Everyday Work Activities and Interactions - Billett, Stephen; Harteis, Christian; Gruber, Hans (The Cambridge Handbook of Expertise and Expert Performance)

FPGA-based Reconfigurable Cache Mapping Schemes: Design and Optimization - Ho, Nam
Traditional cache design uses a consolidated block of memory address bits to index a cache set, equivalent to the use of modulo functions. While this module-based mapping scheme is widely used in contemporary cache structures due to the simplicity of its hardware design and its good performance for sequences of consecutive addresses, its use may not be satisfactory for a variety of application domains having different characteristics.This thesis presents a new type of cache mapping scheme, motivated by programmable capabilities combined with Nature-inspired optimization of reconfigurable hardware. This research has focussed on an FPGA-based evolvable cache structure of the first level cache in a multi-core processor architecture, able to dynamically change cache indexing. To solve the challenge of reconfigurable cache mappings, a programmable Boolean circuit based on a combination of Look-up Table (LUT) memory elements is proposed. Focusing on optimization aspects at the system level, a Performance Measurement Infrastructure is introduced that is able to monitor the underlying microarchitectural metrics, and an adaptive evaluation strategy is presented that leverages on Evolutionary Algorithms, that is not only capable of evolving application-specific address-to-cache-index mappings for level one split caches but also of reducing optimization times. Putting this all together and prototyping in an FPGA for a LEON3/Linux-based multi-core processor, the creation of a system architecture reduces cache misses and improves performance over the use of conventional caches.

Oblique incidence of semi-guided planar waves on slab waveguide steps: effects of rounded edges - Ebers, Lena; Hammer, Manfred; Förstner, Jens (Optics Express)
Oblique propagation of semi-guided waves across slab waveguide structures with bent corners is investigated. A critical angle can be defined beyond which all radiation losses are suppressed. Additionally an increase of the curvature radius of the bends also leads to low-loss configurations for incidence angles below that critical angle. A combination of two bent corner systems represents a step-like structure, behaving like a Fabry-Perot interferometer, with two partial reflectors separated by the vertical height between the horizontal slabs. We numerically analyse typical high-index-contrast Si/SiO2 structures for their reflectance and transmittance properties. When increasing the curvature radius the resonant effect becomes less relevant such that full transmittance is reached with less critical conditions on the vertical distance or the incidence angle. For practical interest 3-D problems are considered, where the structures are excited by the fundamental mode of a wide, shallow rib waveguide. High transmittance levels can be observed also for these 3-D configurations depending on the width of the rib.
Keywords: tet_topic_waveguide

Dynamic Voluntary Provision of Public Goods: The Recursive Nash Bargaining Solution - Hoof, Simon (Static & Dynamic Game Theory: Foundations & Applications)

Modeling Deliberative Argumentation Strategies on Wikipedia - Al Khatib, Khalid; Wachsmuth, Henning; Lang, Kevin; Herpel, Jakob; Hagen, Matthias; Stein, Benno (Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers))

Before Name-Calling: Dynamics and Triggers of Ad Hominem Fallacies in Web Argumentation - Habernal, Ivan; Wachsmuth, Henning; Gurevych, Iryna; Stein, Benno (Proceedings of the 2018 Conference of the North American Chapter of the Association for Computational Linguistics: Human Language Technologies, Volume 1 (Long Papers))

SemEval-2018 Task 12: The Argument Reasoning Comprehension Task - Habernal, Ivan; Wachsmuth, Henning; Gurevych, Iryna; Stein, Benno (Proceedings of The 12th International Workshop on Semantic Evaluation)

Retrieval of the Best Counterargument without Prior Topic Knowledge - Wachsmuth, Henning; Syed, Shahbaz; Stein, Benno (Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers))

Congestion Games mit gewichteten Strategien - Koop, Samuel

ML-Plan for Unlimited-Length Machine Learning Pipelines - Wever, Marcel Dominik; Mohr, Felix; Hüllermeier, Eyke (ICML 2018 AutoML Workshop)
In automated machine learning (AutoML), the process of engineering machine learning applications with respect to a specific problem is (partially) automated. Various AutoML tools have already been introduced to provide out-of-the-box machine learning functionality. More specifically, by selecting machine learning algorithms and optimizing their hyperparameters, these tools produce a machine learning pipeline tailored to the problem at hand. Except for TPOT, all of these tools restrict the maximum number of processing steps of such a pipeline. However, as TPOT follows an evolutionary approach, it suffers from performance issues when dealing with larger datasets. In this paper, we present an alternative approach leveraging a hierarchical planning to configure machine learning pipelines that are unlimited in length. We evaluate our approach and find its performance to be competitive with other AutoML tools, including TPOT.
Keywords: automated machine learning; complex pipelines; hierarchical planning

Proceedings of the 30th on Symposium on Parallelism in Algorithms and Architectures

What are the Drivers of Tax Complexity for MNCs? Global Evidence - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (Intertax)
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments-for example, those triggered by the BEPS project-have given rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this article, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax consultants from 108 countries. Our results show that prior complexity drivers of the tax code are still important, with details and changes of tax regulations being the two most important complexity drivers. We also find evidence for new important complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the tax consultants' responses, we develop a concept of tax complexity that is characterized by two pillars, tax code and tax framework complexity and illustrates the various aspects that should be considered when assessing the complexity of a country's tax system.

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)
DNA origami nanostructures are versatile substrates for the controlled arrangement of molecular capture sites with nanometer precision and thus have many promising applications in singlemolecule bioanalysis. Here, we investigate the adsorption of DNA origami nanostructures in nanohole arrays which represent an important class of biosensors and may benefit from the incorporation of DNA origami-based molecular probes. Nanoholes with well-defined diameter that enable the adsorption of single DNA origami triangles are fabricated in Au films on Siwafers by nanosphere lithography. The efficiency of directed DNA origami adsorption on the exposed SiO2 areas at the bottoms of the nanoholes is evaluated in dependence of various parameters, i.e., Mg2+ and DNA origami concentrations, buffer strength, adsorption time, and nanohole diameter. We observe that the buffer strength has a surprisingly strong effect on DNA origami adsorption in the nanoholes and that multiple DNA origami triangles with 120 nm edge length can adsorb in nanoholes as small as 120 nm in diameter. We attribute the latter observation to the low lateral mobility of once adsorbed DNA origami on the SiO2 surface, in combination with parasitic adsorption to the Au film. While parasitic adsorption can be suppressed by modifying the Au film with a hydrophobic self-assembled monolayer, the limited surface mobility of the adsorbed DNA origami still leads to poor localization accuracy in the nanoholes and results in many DNA origami crossing the boundary to the Au film even under optimized conditions. We discuss possible ways to minimize this effect by varying the composition of the adsorption buffer, employing different fabrication conditions, or using other substrate materials for nanohole array fabrication.

On unification of solutions to the bargaining problem - Haake, Claus-Jochen; Qin, Cheng-Zhong
We establish axioms under which a bargaining solution can be found by the maximization of the CES function and is unique up to specification of the distribution and elasticity parameters. This solution is referred to as the CES solution which includes the NASH and egalitarian solutions as special cases. Next, we consider a normalization of the CES function and establish axioms, under which a bargaining solution can be found by the maximization of the normalized CES and is unique up to the specifications of the distribution and its substitution parameters. We refer to this solution as the normalized CES solution, which includes the Nash and Kalai-Smorodinsky solutions as special cases. Our paper contributes to bargaining theory by establishing unified characterizations of existing as well as a great variety of new bargaining solutions.
Keywords: Bargaining problem; CES Function; Normalized CES Function; Nash solution; Kalai-Smorodinsky Solution; Egalitarian Solution.

Cloud Architectures for Searchable Encryption - Blömer, Johannes; Löken, Nils (Proceedings of the 13th International Conference on Availability, Reliability and Security, ARES 2018)

Thoughts on Social Design - Trockel, Walter; Haake, Claus-Jochen (Studies in Economic Design)
One of the fundamental problems in applications of methods and results from mechanism design and implementation theory is the effective enforcement of theoretically established equilibria by which social choice rules are implemented. Hurwicz (2008) and Myerson (2009) introduce different concepts of formalizing enforcement of institutional rules via the introduction of legal and illegal games. In this note the relation of their concepts with that of a social system defined inDebreu (1952) is analyzed and its potential of being instrumental for modelling institution design is discussed. The existence proof for such a system, also known as generalized game or abstract economy had been the basis for the existence proof of a competitive equilibrium of an economy.

The Influence of Bribery and Relative Reciprocity on a Physician's Prescription Decision - An Experiment - Hilleringmann, Vanessa
Focusing on a physician's relationship to a briber and a patient, this experiment analyzes the influence of a bribe on a physician's treatment decision. We conduct a partner treatment, in which briber and physician play together for the whole experiment and a stranger treament, where briber and physician are re-matched every period. With the help of the two treatments, we vary the relative reciprocity between the physician and the two other actors, briber and patient. Additionally we use a follow up questionnaire to measure the behavioral motivation of the participants. We find that reciprocity leads to bribery relationships: In the partner treatment physicians act corruptly more often. Just the variation of the relative reciprocity between the treatments shows differences in the behavior of the subjects. Differences in the participants' preferences deliver no explanation for their behavior in our experiment.
Keywords: Corruption; Reciprocity; Physician-Patient Relationship